The Relationship Between Parenting Style and Internet Addiction among Adolescents in Banda Aceh - Atika, Syarifa; Fitria, Nayla; Hidayati, Husna (POLITEKNIK KESEHATAN KEMENTERIAN KESEHATAN MANADO, 2024)
Introduction: Internet addiction is a concerning and attention-grabbing phenomenon, especially among adolescents. The internet has led teenagers to become addicted due to its offering of various information, games, and entertainment. This is indicated by the feeling of joy felt when using the internet, the increasing duration of internet use, as well as feelings of anxiety and boredom when having to spend time without internet access. Parenting style emerged as a notable factor influencing internet addiction in teenagers. Objectives: to identify the relationship between parenting styles and internet addiction among adolescents in Banda Aceh. Methods: This study adopted a correlational descriptive approach, with 571 students from the tenth and eleventh grades in high schools in Banda Aceh. The sampling technique employed was proportionate stratified random sampling involving 236 respondents. Measurement tools included the Parental Authority Questionnaire (PAQ) and the Internet Addiction Test (IAT). Data analysis utilized the Spearman Rank Correlation test. Data was collected through Google Forms. Results: a discernible relationship between parental parenting styles and internet addiction, with a p-value of 0.002 < 0.05 and a correlation coefficient of -0.203. Conclusions: a correlation between parenting styles and internet addiction among adolescents in Banda Aceh.